Hannah Jackson - Wagner, Sherry Kafka (Book collections on Project MUSE., 2020)
Hannah Jackson is a story about family and place. In the early twentieth century, a married man in a small Texas town accidentally encounters Hannah, a young woman with no family. He falls in love. In defiance of the town's mores, he leaves his wife, marries his love, and takes her to live on a ranch, away from the community's condemnation. Yet in spite of love and commitment, the couple cannot escape the town's judgment. One particular event that shocks their relationship will affect the rest of their lives. During the years that follow, a web is woven that enmeshes not only the lovers, but their three children as well. Growing up, the young ones find themselves tangled in their parents' predicament. When they become young adults striving to find an identity and a place in the world, their struggles are marked by the effects of family and place. Each character must decide to stay or to leave, and whatever choice they make, the cost will be high.First published in 1966, Hannah Jackson chronicles the turbulence of the '60s and remains a highly relevant novel depicting the oppression of social conventions during times of change.